Marketing Strategy of Arak Gwan Gwan Hoo as Singaraja's Local Culinary in The New Normal Era (Lembaga Pengembangan Kinerja Dosen, 2025)
Marketing of local culinary products in the post-pandemic era is necessitated by adaptation to significant changes in consumers’ habits and behavior. Arak Gwan Gwan Hoo, a traditional Balinese beverage of significant historical and cultural importance, is produced by Arak Gwan Gwan Hoo (GGH) Company, the oldest rice arak manufacturer in Singaraja, established in 1920. Therefore, this study aimed to analyze the marketing strategy carried out by Arak Gwan Hoo Bali in the New Normal era. A qualitative method was adopted with a focus on data collection through interviews and observations, which was then analyzed using SWOT (Strength, Weakness, Opportunity, Threat). The results show that the applicable marketing strategy to increase sales of Arak Gwan Gwan Hoo includes several main steps, namely business restructuring, product diversification, and expanding market access. Optimization of the main strategy was carried out through a retrenchment method by reducing assets and costs to increase operational efficiency. Furthermore, the implementation of a diversification strategy, both concentric, horizontal, and conglomerate, enables the company to expand its product line and adjust the offerings to market needs. Other strategic steps include divestment or reduction of unproductive assets and liquidation of less profitable parts of the business.